THE INFLUENCE OF SHOPEE INDONESIA‘S INSTAGRAM CONTENT MARKETING ON E-CUSTOMER LOYALTY WITH CUSTOMER ENGAGEMENT AS A MEDIATION VARIABLE - Fitrisam, Syarifah Aliyah; Rombe, Elimawati; Muzakir, Muzakir (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2022)
This study aims to determine the influence of content marketing on Shopee Indonesia's official Instagram account on e-customer loyalty with customer engagement as mediating variable. This is descriptive-causal research. The research sample was 100 Shopee Indonesia customers who engaged on the official Shopee Indonesia Instagram account which was determined using the purposive sampling method. This study used Partial Least Square (PLS) to test the hypothesis with the help of SmartPLS software. The results of this study indicate that (1) content marketing has no significant influence on e-customer loyalty (2) content marketing has a positive and significant influence on customer engagement, (3) customer engagement has a positive and significant influence on e-customer loyalty, (4) customer engagement mediates the influence of content marketing on e-customer loyalty. This study contributes to the digital marketing literature, particularly on content marketing, engagement, and e-customer loyalty discussion. Keywords: Content Marketing, Customer Engagement, E-Customer Loyalty